Seismic Analysis for Multi-Story Building Horizontally Damped Above Basement Level - Ziauddin Patowary, Mohammed; Kadir Marsono, Abdul (International Journal of Engineering and Technology, 2018)
Due to the urbanization multi-story building with underground story for parking space and storage are very common in practice. Now a day, seismic energy dissipating devices are being used for various types of structures and located in basements which are difficult to maintain.Â The main objective is to evaluate the effectiveness of horizontal dampers in the ground floor level of the multi-story building above basement. Among different types of dampers, visco-elastic [VE] dampers are used for this numerical study. Comparing with other types of passive energy dissipating devices, visco-elastic [VE] dampers are considered most suitable. For the better understanding of the effectiveness of horizontal dampers, stiff foundation system is considered thus soil-structure interaction is omitted. In this numerical study, seismic response of different hypothetical structures analyzed having different underground stories and horizontal dampers only in the ground level. Modeling and analysis of the structures and installation of the dampers are done by using finite element modeling software [ETABS]. Time history analysis was used to simulate the response of the structures. Sabah earthquake [05/June/2015] with the PGA of 0.126g was used for the time history analysis. Different dynamics parameters such as natural time period, displacement, base shear and inter-story drift were evaluated. Changes in the results among the structures demonstrated the efficiency of horizontal dampers. Optimum locations of the horizontal dampers were also revealed in this study in the basis of the analysis results.Â Â